Crosstalks between mTORC1 and mTORC2 variagate cytokine signaling to control NK maturation and effector function. Issue 1 (December 2018) - Wang, Fangjie; Meng, Meng; Mo, Banghui; Yang, Yao; Ji, Yan; Huang, Pei; Lai, Wenjing; Pan, Xiaodong; You, Tingting; Luo, Hongqin; Guan, Xiao; Deng, Yafei; et al.
Abstract The metabolic checkpoint kinase mechanistic/mammalian target of rapamycin (mTOR) regulates natural killer (NK) cell development and function, but the exact underlying mechanisms remain unclear. Here, we show, via conditional deletion of Raptor (mTORC1) or Rictor (mTORC2), that mTORC1 and mTORC2 promote NK cell maturation in a cooperative and non-redundant manner, mainly by controlling the expression of Tbx21 and Eomes. Intriguingly, mTORC1 and mTORC2 regulate cytolytic function in an opposing way, exhibiting promoting and inhibitory effects on the anti-tumor ability and metabolism, respectively. mTORC1 sustains mTORC2 activity by maintaining CD122-mediated IL-15 signaling, whereas mTORC2 represses mTORC1-modulated NK cell effector functions by restraining STAT5-mediated SLC7A5 expression. These positive and negative crosstalks between mTORC1 and mTORC2 signaling thus variegate the magnitudes and kinetics of NK cell activation, and help define a paradigm for the modulation of NK maturation and effector functions. The metabolic regulator protein family, mTOR, regulate natural killer (NK) cell development and function, but the underlying mechanism is unclear. Here, the authors show that Raptor/mTORC1 and Rictor/mTORC2 form a feedback crosstalk network to variegate cytokine and cellular signaling and modulate NK maturation and effector functions.